Penerapan Metode Tutor Sebaya untuk Meningkatkan Motivasi dan Hasil Belajar Siswa pada Mata Pelajaran Estimasi Biaya Konstruksi dan Properti - Ambara, Agung Pria; Supardji, Supardji (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
Student motivation and learning outcomes are important aspects of the learning process that determine the success of education. This study aims to analyse the effectiveness of the application of the peer tutor method in improving student motivation and learning outcomes. The results of the study show that the peer tutor method can increase students' motivation to learn through more active interaction, a pleasant learning atmosphere, and emotional support from peers. The application of the peer tutor method provides opportunities for students to share knowledge with each other, strengthen the concepts learned, and increase their confidence in completing learning tasks. This study recommends that this method be applied sustainably with good management to create more meaningful and inclusive learning.